Assessment of Microbial Load in Regional Hospitals in Albania - Koja, Gjergji; Piligriu, Florenc; Simaku, Artan; Qyra, Shpetim; Abazaj, Erjona (Open Access Macedonian Journal of Medical Sciences, 2022)
Background Contaminated hospital indoor environments can expose patients to microorganisms and different infections. The aimed study was to assess the microbial load in hospital facilities inside Albania Regional Hospitals during the period 2017-2019. Methods A cross-sectional study was conducted during the period 2017-2019 for the assessment of microbial contamination in operating rooms, resuscitation, and delivery rooms in 12 regional hospitals in Albania. One thousand and three hundred microbiological specimens were collected from air and surfaces using 5% sheep blood agar (Oxoid, UK) and processed at IPH microbiology laboratory following the standard bacteriological procedures Data were analyzed using Statistical Software Package for Social Sciences (SPSS) version 23. Results Out of the total number of samples, 1148 (88.3%) were collected from surfaces and 152 (11.7%) were from the air. Bacterial growth was identified in 314 (24.2%) out of 1300 samples (95% CI 21.89–26.62). From the total site samples processed during the study period, bacterial growth showed 282 (89.8%) samples from surfaces and 32 (10.2%) air samples. There was found a significant association p-value =0.035. Regarding the sampling place collection, the largest number were collected in operating rooms (60.3%) followed by emergency rooms (28.2%), ICUs (7.7%), and maternity units (3.8%). Gram-negative isolates were predominant at 235 (74.8%), while the Gram-positive were at 60 (19.1%). E. coli was the most frequent bacterial isolate (50%) followed by Pseudomonas aeruginosa (23.6%), Staphylococcus aureus (19.1%), and Klebsiella pneumoniae (1.3%). Also, we found a fungal agent such as Aspergillus in 19 (6.1%) samples. The isolated bacteria’s overall drug resistance profile revealed that 66.8% of gram-positive bacteria were resistant to two or more antimicrobial drugs tested. Conclusion This study revealed that the surface and air and air within different wards of the hospitals studied were contaminated with different types of bacteria. Bacterial loads on the surface and air exceeded normal limits. Additionally, the study pointed out high levels of antimicrobial resistance to the drugs commonly prescribed for isolates. Therefore, intervention strategies need to be strengthened to expand infection prevention practices in hospitals. Continuous monitoring and monitoring of in-hospital pathogen types and susceptibility patterns should be performed on a very regular basis.